Pandemic Era Students Readiness for Business in Jakarta - Krisnanto, Umbas (Archives of Business Research, 2020)
This study aims to decide starting up a business for students in pandemic era. This study uses factor analysis data collection techniques using a questionnaire. The sample was college students. The results that entrepreneurship will be easier because it can create its own brand, can take advantage of social media, supported by the ability to use current technology. Entrepreneurship can be started at any time and start with yourself and your own efforts with the hope that in the future can have a better life for yourself. The entrepreneurship starts with how to start a business by doing business planning. Entrepreneurship requires a supportive educational background. Entrepreneurship can be through learning that has been done by family or advice from parents or culture that has been formed.